Spectral characterization of optical aberrations in fluidic lenses - Puentes, Graciana; Minotti, Fernando (Frontiers in Physics, 2024)
We report an extensive numerical study and supporting experimental results on the spectral characterization of optical aberrations in macroscopic fluidic lenses with tunable focal distance and aperture shape. Using a Shack-Hartmann wave-front sensor we experimentally reconstruct the near-field wave-front transmitted by the fluidic lenses, and we characterize the chromatic aberrations in terms of Zernike polynomials in the visible range. Moreover, we further classify the spectral response of the lenses using clustering techniques, in addition to correlation and convolution measurements. Experimental results are in agreement with our theoretical model of the non-linear deformation of thin elastic membranes.